Conductive film and method for producing same
By adopting a new metal oxide thin film chemical structure (AO)2B6O11 and adjusting the oxidation state by introducing external metal elements to form a layered structure, the existing problem of low conductivity is solved, and higher conductivity and lower heat loss are achieved.
Patent Information
- Application Number
- JP2023543912
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-27
- Filing Date
- 2022-08-22
- Publication Date
- 2025-04-17
- Estimated Expiration
- 2042-08-22
AI Technical Summary
In the prior art, the conductive metal oxide film has low electrical conductivity, resulting in large heat and power losses caused by the equipment during operation.
A new metal oxide film is used, and the chemical formula is (AO)2B6O11, where A is a metal element that can be valent +1 or +2, and B is a transition metal element that can be valent +4 or +5. The oxidation state is adjusted by introducing external metal elements to form a layered metal oxide film.
The conductive metal oxide film is improved, making its conductivity higher than that of traditional conductive metal oxide films, and reducing the heat loss and power consumption of the equipment.
Smart Images

Figure 0007663914000001 
Figure 0007663914000002 
Figure 0007663914000003
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application is based on Japanese Patent Application No. 2021-139234, filed on August 27, 2021, the contents of which are incorporated herein by reference. [Technical field]
[0002] The present disclosure relates to a conductive film containing a metal oxide as a main component and a method for producing the same. [Background technology]
[0003] In recent years, functional devices have been developed for a stable supply of resources and a sustainable society. Physical elements such as solar cells, transistors, memory elements, thermoelectric elements, and physical sensors are composed of multiple laminated thin films. The multiple thin films include a film composed of an oxide of a transition metal as the element material. An electrode composed of a conductive film with high electrical conductivity is laminated on the film composed of the element material. As the conductive film, it is preferable to use a conductive film mainly composed of a conductive metal oxide that has a similar crystal structure and chemical bond to the element material.
[0004] As such a conductive film, a conductive film mainly composed of Ti2O3, in which the ratio of Ti to O is smaller than that of TiO2, is disclosed in Non-Patent Document 1. The electrical conductivity of this conductive film is 1.7×10 3 S cm -1 This film was prepared by subjecting the raw material, Ti2O3 sintered body, to 1000°C and oxygen partial pressure of 1×10 -3 It is fabricated on an insulating substrate by laser ablation under Torr. [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] K. Yoshimatsu, H. Kurokawa, K. Horiba, H. Kumigashira, and A. Ohtomo, “Large anisotropy in conductivity of Ti2O3 films,” APL Materials 6, 101101 (2018). Summary of the Invention
[0006] However, the electrical conductivity of conventional conductive films mainly composed of the above-mentioned conductive metal oxides is low, 1 / 250 that of aluminum, which is an elemental metal, and 1 / 352 that of copper. Low electrical conductivity of a conductive film can cause significant heat generation and power loss in devices. For this reason, there is a demand for the development of a conductive film mainly composed of a conductive metal oxide that has higher electrical conductivity than conventional conductive films.
[0007] The present disclosure provides a conductive film with an electrical conductivity of 1.7 × 10 3 S cm -1 The present invention aims to provide a conductive film mainly composed of a metal oxide, which has a higher electrical conductivity than that of the conventional conductive film, and a method for producing the same.
[0008] In order to achieve the above object, according to one aspect of the present disclosure, The conductive film contains a metal oxide as a main component, The metal oxide has the same components as a compound represented by the following formula (I), and has a crystal structure in which a diffraction peak appears in an X-ray diffraction pattern at the same diffraction angle as a diffraction peak appears in the X-ray diffraction pattern of the compound represented by the following formula (I), (AO)2B6O 11 (I) In formula (I), A is a metal element that can have a valence of +1 or +2. In formula (I), B is a transition metal element that can have a valence of +4 or +5; In formula (I), O is an oxygen element. The average valence of B in formula (I) is less than the maximum oxidation number of B.
[0009] The conductive metal oxides used in conventional conductive films have an insulating structure in which BO6 octahedra are connected three-dimensionally, but donor impurities and regular oxygen vacancies are introduced so that the valence of B is less than the maximum oxidation number. However, these donor impurities and oxygen vacancies exist within the BO6 octahedron, which is the conduction path for electrons. Therefore, the donor impurities and oxygen vacancies act as electron scatterers inside the BO6 octahedron, preventing the improvement of electrical conductivity. This is the reason why conventional conductive films, which are mainly composed of conductive metal oxides, have low electrical conductivity.
[0010] In contrast, in the conductive metal oxide of the present disclosure used in the conductive film of the present disclosure, one or more metal elements are added to a binary oxide of a transition metal element that can have a valence of +4 or +5. As a result, the metal oxide of the present disclosure has a crystal structure in which one type of unit structure in a layered form in which a plurality of BO6 octahedra are connected in layers is repeatedly arranged, and an element A exists in the gap between the unit structures in the unit structures. According to this, the element A as a donor impurity that supplies electrons exists outside the unit structures. In other words, there is no donor impurity that scatters electrons inside the BO6 octahedra of the unit structures. Therefore, electrons can be conducted inside the clean BO6 octahedra with little disorder of the unit structures. Therefore, it is possible to provide a conductive film mainly composed of a conductive metal oxide, which has a higher electrical conductivity than conventional conductive films.
[0011] According to another aspect of the present disclosure, The present invention relates to a compound having the same components as a compound represented by the following formula (I), and comprising, as a main component, a metal oxide having a crystal structure in which a diffraction peak appears at the same diffraction angle in an X-ray diffraction pattern as a diffraction peak appears in an X-ray diffraction pattern of the compound represented by the following formula (I), (AO)2B6O 11 (I) In formula (I), A is a metal element that can have a valence of +1 or +2. In formula (I), B is a transition metal element that can have a valence of +4 or +5; In formula (I), O is an oxygen element. The method for producing a conductive film, in which the average valence of B in formula (I) is less than the maximum oxidation number of B, comprises the steps of: Providing a substrate; forming the conductive film on the surface of the substrate by a laser ablation method performed in an atmosphere containing oxygen gas using a target containing the same element as A in formula (I) and the same element as B in formula (I).
[0012] As explained in the above aspect, the conductive film produced by this production method has a higher electrical conductivity than conventional conductive films. Therefore, this production method makes it possible to produce a conductive film mainly composed of a conductive metal oxide, which has a higher electrical conductivity than conventional conductive films.
[0013] Note that the reference symbols in parentheses attached to each component indicate an example of the correspondence between the component and specific components described in the embodiments described below. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view of a conductive film laminate in which a conductive film and a substrate are laminated in an embodiment. [Diagram 2] FIG. 1 shows a unit cell of (BaO)2Ti6O11. [Figure 3A] FIG. 1 shows the crystal structure of (BaO)2Ti6O11. [Figure 3B] FIG. 1 shows the crystal structure of (BaO)2Ti6O11. [Figure 4] 1 is a flowchart showing a method for manufacturing a conductive film in an embodiment. [Diagram 5] FIG. 1 shows an X-ray diffraction pattern of a thin film of (BaO)2Ti6O11. [Figure 6A] FIG. 1 shows transmission electron microscope (TEM) bright-field images (BF) of a SrTiO3 substrate and a thin film of (BaO)2Ti6O11. [Figure 6B] FIG. 2 is a diagram showing a transmission electron microscope (TEM) diffraction pattern of a SrTiO3 substrate. [Figure 6C] FIG. 1 shows transmission electron microscope (TEM) diffraction patterns of a SrTiO3 substrate and a thin film of (BaO)2Ti6O11. [Figure 7] FIG. 1 shows a bright-field image (BF-STEM image) of a scanning transmission electron microscope (STEM) and a high-angle-angle-diffusion dark-field image (HAADF-STEM image) of a thin film of (BaO)2Ti6O11. [Figure 8] This is a HAADF-STEM image of a thin film of (BaO)2Ti6O11, with the atomic arrangement of (BaO)2Ti6O11 superimposed on it. [Figure 9] FIG. 1 shows the temperature dependence of electrical conductivity of a thin film of (BaO)2Ti6O11. [Figure 10] FIG. 1 is a diagram showing the temperature dependence of the electrical conductivity of a (BaO)2Ti6O11 thin film which is the conductive film of Example 1, a SrRuO3 thin film which is the conductive film of Comparative Example 1, and a SrTiO3-X thin film which is the conductive film of Comparative Example 2. [Figure 11] FIG. 1 is a graph showing the film thickness dependence of electrical conductivity of each of the (BaO)2Ti6O11 thin films in Examples 1, 2, and 3. [Figure 12] FIG. 1 is a graph showing the temperature dependence of the electrical conductivity of a sintered body of (BaO)2Ti6O11. [Figure 13] FIG. 1 shows the density of states of (BaO)2Ti6O11 calculated by density functional theory (DFT). [Figure 14A] FIG. 1 shows an electron density map in the ac plane of (BaO)2Ti6O11 calculated by DFT. [Figure 14B] FIG. 1 shows an electron density map in the bc plane of (BaO)2Ti6O11 calculated by DFT. [Figure 15A] 1 shows the results of measuring the electron energy loss spectroscopy (EELS) spectrum of the (BaO)2Ti6O11 film of Example 1. [Figure 15B] FIG. 15B is a diagram showing the ratio of Ti4+ and Ti3+ components obtained from the EELS analysis results of FIG. 15A in Example 1 etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] A conductive film according to an embodiment of the present disclosure will be described with reference to FIG. 1. The conductive film 11 shown in FIG. 1 is a film having electrical conductivity, i.e., electrical conductivity. The conductive film 11 may be a thin film having a thickness of about 2 μm or less. The conductive film 11 provides electrical contact with one or more substances deposited thereon. The conductive film 11 is used as an electrode of a physical element, such as a solar cell, a transistor element, a memory element, a thermoelectric element, or a physical sensor element.
[0016] 1, the conductive film 11 is disposed on the substrate 12 in contact with the surface of the substrate 12. The conductive film 11 constitutes a conductive film laminate 13 in which the conductive film 11 and the substrate 12 are laminated. The conductive film 11 has any outer shape according to the shape of the substrate 12 (e.g., a rectangular plate shape, a disk shape, etc.). The substrate 12 has a main surface and a back surface. The conductive film 11 is deposited on the main surface side of the substrate 12.
[0017] Conductive film 11 contains a metal oxide as a main component. "Contains a metal oxide as a main component" means that the metal oxide accounts for 90 at.% or more of the entire conductive film 11. Thus, conductive film 11 may be composed of only metal oxide, or conductive film 11 may contain impurities, etc., resulting from the raw materials of the metal oxide, in addition to the metal oxide, or small amounts of other components may be added to conductive film 11 during the process of forming the metal oxide.
[0018] The metal oxide of this embodiment contained as a main component in the conductive film 11 has a basic composition of a compound represented by the following formula (I). (AO)2B6O 11 (I) A in formula (I) is a metal element that can have a valence of +1 or +2. B in formula (I) is a transition metal element that can have a valence of +4 or +5. O in formula (I) is an oxygen element. The average valence of B in formula (I) is less than the maximum oxidation number of B.
[0019] The metal oxide of this embodiment has a specific crystal structure. First, (BaO)2Ti6O, which is an example of the compound of formula (I), 11 The crystal structure of (BaO)2Ti6O is explained. 11 is a compound in which A in formula (I) is Ba and B in formula (I) is Ti.
[0020] Figure 2 shows the structure of (BaO)2Ti6O 11 The unit cell of powdered (BaO)2Ti6O is shown. 11 The lattice constants are a = 15.16 Å, b = 3.893 Å, c = 9.093 Å, α = 90°, β = 98.6°, and γ = 90°.
[0021] Ba is +2 and O is -2. Considering this, (BaO)2Ti6O 11 In addition to the common valence of +4, Ti in the crystal also contains +3 valence. With this change in valence, (BaO)2Ti6O 11 The valence of the ions in the crystal is (Ba 2+ O 2- )2(Ti 4+ 4, Ti 3+ 2) O 2- 11 Also, (BaO)2Ti6O 11 In this case, the valence of all O is (-2) x 13 = -26, and the valence of all Ba is (+2) x 2 = +4. To maintain charge neutrality, the valence of all Ti is +22. (BaO)2Ti6O 11 The average valence of Ti in is +22÷6≒+3.7. Thus, the average valence of Ti is smaller than the maximum oxidation number of Ti, which is +4. In this way, because the average valence of Ti is less than the maximum oxidation number of Ti, conductive electrons are secured, resulting in high electrical conductivity.
[0022] FIG. 3A shows (BaO)2Ti6O viewed from a direction parallel to the c-axis. 11 FIG. 3B shows the crystal structure of (BaO)2Ti6O as viewed parallel to the b-axis. 11 As shown in Figures 2, 3A and 3B, (BaO)2Ti6O 11has a crystal structure in which one type of unit structure in layers, in which a plurality of TiO6 octahedra are connected in layers, is repeatedly arranged, and Ba exists in the gaps between the unit structures in the unit structures. Some of the plurality of TiO6 octahedra are TiO5 octahedra. In FIG. 2, a plurality of TiO6 octahedra are connected in one direction to form a TiO6 octahedron group, and the portion where the TiO6 octahedron group overlaps is a unit structure. In the crystal structure shown in FIG. 3A, the portion indicated by the arrow d is a unit structure in which TiO6 octahedra are connected in layers. In the portion indicated by the arrow e in the crystal structure shown in FIG. 3A, the unit structures are connected to each other by Ba-O bonds.
[0023] The metal oxide of this embodiment is (BaO)2Ti6O 11 It has the same crystal structure as
[0024] The metal oxide of this embodiment is not limited to a compound in which B in formula (I) is only Ti, but may be a compound in which B in formula (I) contains Ti and other elements different from Ti. In this case, the other elements are one or more elements selected from V (vanadium), Cr (chromium), Mn (manganese), Fe (iron), Co (cobalt), Nb (niobium), Ru (ruthenium), Pd (palladium), Ta (tantalum), W (tungsten), Mo (molybdenum), Re (rhenium), Os (osmium), Ir (iridium) and Pt (platinum). These elements are metal elements with an ionic radius of 0.60 Å to 0.675 Å that are known to have a valence of +2 to +4. The other elements partially substitute Ti in the compound in which B in formula (I) is only Ti. For this reason, other elements are selected that fall within the range of ion radii of 0.60 Å (+4 valence) to 0.675 Å (+3 valence), which corresponds to the valence that Ti can take.
[0025] The metal oxide of this embodiment may be a compound in which B in formula (I) is at least one of Ta and Nb, which can have a valence of +5. Both Ta5+ and Nb5+ have an ionic radius close to that of Ti4+. Therefore, this compound is also (BaO)2Ti6O 11It is believed that the crystal structure is the same as that of
[0026] The metal oxide of this embodiment may be a compound in which B in formula (I) contains at least one of Ta and Nb, and another element different from Ta and Nb. In this case, the other element is one or more elements selected from Ti (titanium), V (vanadium), Mn (manganese), Fe (iron), Co (cobalt), Ru (ruthenium), Rh (rhodium), Ir (iridium), Mo (molybdenum), and W (tungsten). These elements are metal elements with an ionic radius of 0.64 Å to 0.68 Å that are known to take a valence of +2 to +4. The other element partially replaces B in a compound in which B in formula (I) is at least one of Ta and Nb. For this reason, an element included in the range of an ionic radius of 0.64 Å (+5 valence) to 0.68 Å (+4 valence), which corresponds to the valence that both Ta and Nb can take, is selected as the other element. As a result, the compound in this case is also (BaO)2Ti6O 11 It is believed that the crystal structure is the same as that of
[0027] (BaO)2Ti6O 11In order to form the same crystal structure as (BaO)2Ti6O11, A in formula (I) is an alkali metal element or an alkaline earth metal element whose ionic radius is in the range of 0.78 Å to 1.73 Å. Specifically, A in formula (I) is one or more elements selected from Ca (calcium), Sr (strontium), Ba (barium), Na (sodium), K (potassium), Rb (rubidium) and Cs (cesium). The element A functions as a donor impurity that supplies electrons. For this reason, the element A is an alkali metal or an alkaline earth metal element with a small electronegativity. Furthermore, the element A fits into the gap of the layered unit structure formed by the TiO6 octahedron. For the ionic radii of 0.60 Å (+4 valence) and 0.67 Å (+3 valence) corresponding to the valences that Ti can take, the calculated distances of the gaps sandwiching the Ba element in the same crystal structure as (BaO)2Ti6O11 are 3.46 Å and 3.12 Å, respectively. For the element A to exist stably in this gap, the gap distance is preferably 2 to 4 times the ionic radius of the element A. If it is less than 2 times, the element A cannot enter the space, which causes a change in the crystal structure, and if it is 4 times or more, the element A cannot be accommodated in a stable atomic position and moves within the gap, making it impossible to obtain a stable crystal structure. Under these conditions, the ionic radius of the element A is determined to be 0.78 Å to 1.73 Å.
[0028] General metal oxides have non-stoichiometry due to oxygen atom vacancies, metal element substitutions, changes in the valence of metal elements, etc. The metal oxide of this embodiment also has the basic composition (AO)2B6O within the range of having the same crystal structure as the compound represented by formula (I). 11The deviation of the composition ratio from the formula (I) is allowed. Therefore, the metal compound of the present embodiment only needs to have the same components as the compound represented by formula (I) and a crystal structure in which a diffraction peak appears at the same diffraction angle as the diffraction angle at which a diffraction peak appears in the X-ray diffraction pattern of the compound represented by formula (I). Here, the description "the metal compound of the present embodiment has the same components as the compound represented by formula (I)" specifies the type of element constituting the metal oxide of the present embodiment. That is, this description means that the metal oxide of the present embodiment has, as components, the element A in formula (I), the element B in formula (I), and an oxygen element. In addition, the description "the metal compound of the present embodiment has a crystal structure in which a diffraction peak appears at the same diffraction angle as the diffraction angle at which a diffraction peak appears in the X-ray diffraction pattern of the compound represented by formula (I)" specifies the composition ratio of the metal compound of the present embodiment. According to this description, the composition ratio of the metal compound of the present embodiment is (AO)2B6O within the range in which the metal compound has the same crystal structure as the compound represented by formula (I). 11 Therefore, from these descriptions, the metal compound of this embodiment includes not only the compound represented by formula (I), but also compounds having the same crystal structure as the compound represented by formula (I), such as (AO)2B6O 11 This also includes compounds whose composition ratios deviate from the above.
[0029] The substrate 12 is a base material used for forming the conductive film 11. The base material is a base material that supports the conductive film 11. The substrate 12 has a crystalline structure. The spacing in one direction in the main surface of the substrate 12 is d. In the crystal structure of the substrate 12, it is preferable that the value of an integer multiple of d is within ±7% of the values of b and c, which are the lattice constants of the compound of formula (I). The crystal plane of the main surface of the substrate 12 is SrTiO3, KTaO3, BaTiO3, DyScO3, GaScO3, LaAlO3, NdGaO3, (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 It is preferable that the substrate 12 has a (210) surface such as (LSAT). In the embodiment described later, a (BaO)2Ti6O11 In this case, the value of the integral multiple of the interplanar spacing d of the (210) plane of the SrTiO3 substrate 12 is (BaO)2Ti6O 11 The value is +0.5% for the lattice constant b and -4% for the lattice constant c.
[0030] 4, the method for manufacturing the conductive film 11 of this embodiment includes a base material preparation step S1 and a film formation step S2. In the base material preparation step S1, a substrate 12 is prepared as a base material. The substrate 12 may be made of any of SrTiO3, KTaO3, BaTiO3, DyScO3, GaScO3, LaAlO3, NdGaO3, (LaAlO3), etc. 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 (LSAT) or at least one of the above is used.
[0031] In the film forming step S2, a conductive film 11 is formed on the surface of a base material. When a substrate 12 is prepared as the base material, the conductive film 11 is formed on the main surface of the substrate 12. The conductive film 11 is formed in an atmosphere containing oxygen gas by a laser ablation method using a target containing the same element as A in formula (I) and the same element as B in formula (I). The conductive film 11 may be formed by other methods that can form a film having crystallinity, without being limited thereto. Other methods include a sputtering method, a molecular beam epitaxy (MBE), a sol-gel method, various chemical vapor deposition (CVD) methods, and the like. The method of forming the conductive film 11 is adopted in consideration of the film quality and film thickness to be formed. In this manner, the conductive film 11 is manufactured.
[0032] In the substrate preparation step S1, a substrate having one or more layers of film formed on the main surface of the substrate 12 may be used as the substrate. In this case, in the film formation step S2, a conductive film 11 is formed on the surface of the film on the main surface of the substrate 12. After being formed on the main surface of a substrate such as the substrate 12, the conductive film 11 may be transferred to another member. The conductive film 11 is not necessarily used integrally with the substrate such as the substrate 12, and may be used separately from the substrate.
[0033] As described above, the conductive film 11 of this embodiment contains the metal oxide of this embodiment as a main component. The metal oxide of this embodiment has the same components as the compound represented by formula (I), and has a crystal structure in which a diffraction peak appears at the same diffraction angle in the X-ray diffraction pattern as the diffraction peak appears in the X-ray diffraction pattern of the compound represented by formula (I).
[0034] Incidentally, the conductive metal oxides used in conventional conductive films have an insulating structure in which BO6 octahedra are three-dimensionally connected, but donor impurities and regular oxygen vacancies are introduced so that the valence of B is less than the maximum oxidation number. Examples of B elements include titanium, tantalum, and niobium. For example, when the B element is Ti, a series of Ti elements, including Ti2O3 and Ti4O7, in which donor impurities and oxygen vacancies of Nb or tin are introduced into insulating TiO2, are n O 2n-1 Conductive metal oxides represented by the formula: are known. However, these donor impurities and oxygen vacancies exist within the BO6 octahedron, which is the conduction path for electrons. Therefore, the donor impurities and oxygen vacancies act as electron scatterers within the BO6 octahedron, preventing improvement of electrical conductivity. This is the reason why conventional conductive films that mainly consist of conductive metal oxides have low electrical conductivity.
[0035] In contrast, in the metal oxide of this embodiment, one or more metal elements are added to a binary transition metal oxide of a transition metal element that can have a valence of +4 or +5. As a result, the metal oxide of this embodiment has a crystal structure in which a single type of unit structure in the form of a layer in which a plurality of BO6 octahedra are connected in layers is repeatedly arranged, and an element A exists in the gap between the unit structures in the unit structures. According to this, the element A as a donor impurity that supplies electrons exists outside the unit structures. In other words, there is no donor impurity that scatters electrons inside the BO6 octahedra of the unit structures. Therefore, electrons can be conducted inside the clean BO6 octahedra with little disorder of the unit structures. Therefore, it is possible to provide a conductive film 11 mainly composed of a conductive metal oxide, which has a higher electrical conductivity than conventional conductive films.
[0036] The method for producing the conductive film 11 of this embodiment includes preparing a substrate 12, and forming the conductive film 11 on the surface of the substrate 12 by a laser ablation method performed in an atmosphere containing oxygen gas using a target containing the same element as A in formula (I) and the same element as B in formula (I). As explained above, the conductive film of this embodiment produced by this production method has a higher electrical conductivity than conventional conductive films. Therefore, this production method can produce a conductive film mainly composed of a conductive metal oxide, which has a higher electrical conductivity than conventional conductive films.
[0037] Furthermore, the electrical conductivity of the conductive film 11 of this embodiment is higher than that of a conventional conductive film mainly composed of a metal oxide, and therefore, when the electrical conductivity is to be the same as that of a conventional conductive film, the thickness of the conductive film 11 of this embodiment can be reduced to one-sixth or less of the thickness of the conventional conductive film.
[0038] Furthermore, as described in the examples below, the conductive film 11 of this embodiment has metallic electrical conductivity, in which the electrical conductivity increases as the temperature decreases, at least in a certain temperature range.
[0039] In addition, it is easily expected that the difference in thermal expansion coefficient between the metal oxide of this embodiment and the metal oxide used as an element material in a physical element is smaller than that of a metal material generally used as an electrode, and therefore the conductive film 11 of this embodiment has the effect of being less likely to peel off from the substrate 12 than a conductive film made of a metal material generally used as an electrode.
[0040] In addition, the metal oxide of this embodiment has a chemical bond and a crystal structure similar to those of metal oxides used as element materials in physical elements. Therefore, when a laminate structure is formed by the conductive film 11 of this embodiment and the element material, good lattice matching can be achieved. Factors that impair element performance, such as defects and interface layers, can be significantly reduced.
[0041] In addition, it is easily expected that the melting point of the metal oxide of this embodiment is higher than that of metal materials generally used for electrodes, and therefore, in a method of manufacturing a physical element using a metal oxide as an element material, a heating process at a higher temperature than that in the case of using metal materials generally used for electrodes can be performed. EXAMPLES
[0042] The present inventors have applied a (BaO)2Ti6O 11 A thin film of was formed by laser ablation. The target used was a sintered body with a molar ratio of Ba:Ti:O of 1:3:x. The substrate surface was the (210) surface of SrTiO3. The laser used was a KrF pulsed laser. The laser fluence (i.e., the laser irradiation energy density) was 0.6 J cm ―2 The spot size of the irradiated laser is 0.024 cm 2 The degree of vacuum in the container in which the substrate was placed during film formation was 1.0×10 -5Pa. The substrate temperature is 1000° C. The laser irradiation frequency is 2 Hz. The conductive film 11 in Example 1 has a thickness of about 100 nm. The conductive film 11 in Example 2 has a thickness of about 200 nm. The conductive film 11 in Example 3 has a thickness of about 20 nm.
[0043] The film forming conditions for the conductive film 11 are not limited to those in Examples 1 to 3. However, the laser fluence is set to the minimum value of 0.5 J cm required for ablation from the target. ―2 It is desirable to set the laser fluence at or below a value at which the ratio of the ablated metal species is kept spatially uniform. The substrate temperature and oxygen partial pressure during ablation should be between 800°C and 1500°C, and between 1×10 -6 Pa or more 1×10 ―3 This is to realize a reducing atmosphere in the chamber that can stabilize the Ti chemical species on the substrate at a value lower than the highest oxidation number during ablation.
[0044] [(BaO)2Ti6O 11 Thin film structure of Figure 5 shows the structure of (BaO)2Ti6O 11 5 shows the X-ray diffraction pattern of the thin film of (BaO)2Ti6O. The X-ray diffraction pattern was measured using SmartLab (Rigaku Corporation, X-ray source CuKα 0.1542 nm). As shown in FIG. 5, (BaO)2Ti6O 11 5. The peaks corresponding to the L00 (L=2, 4, 6, 8, 10, 12) plane were observed, which indicates that the conductive film 11 is oriented along the a-axis with respect to the main surface of the substrate 12. The * in FIG. 5 corresponds to the (210) diffraction peak of SrTiO3.
[0045] 6A to 6C show (BaO)2Ti6O 11 FIG. 6A is a diagram for explaining the results of structural analysis of the thin film of SrTiO3 substrate and (BaO)2Ti6O 11 FIG. 6B shows a TEM bright field image of the thin film of SrTiO3 substrate 12 alone. FIG. 6C shows a TEM bright field image of the thin film of SrTiO3 substrate 12 and (BaO)2Ti6O11 6C shows a TEM diffraction pattern of a thin film of (BaO)2Ti6O shown in FIGS. 2, 3A, and 3B. The lattice constant in the thin film is slightly different from that in the powder due to the constraint from the substrate 12. However, the TEM diffraction pattern shown in FIG. 6C is the same as that of the (BaO)2Ti6O 11 This roughly matches the theoretical diagram calculated based on the atomic arrangement of (BaO)2Ti6O 11 The thin film of (BaO)2Ti6O shown in Figs. 2, 3A and 3B 11 These structural analysis results showed that the compound has a crystal structure similar to that of
[0046] Figure 7 shows the structure of (BaO)2Ti6O 11 These STEM images were measured using an ARM-200FC (JEOL Ltd.) equipped with a 200 kV spherical aberration corrector. 11 The thin film had a layered structure as shown by the arrows in Figure 7. 11 The HAADF-STEM image of the thin film of (BaO)2Ti6O shown in Figure 3A 11 (BaO)2Ti6O 11 The thin film is (BaO)2Ti6O shown in FIG. 11 It was shown that it has a similar crystal structure to that of
[0047] [(BaO)2Ti6O 11 Electrical properties of thin films of The present inventors have investigated the conductive film 11 of Example 1, which is (BaO)2Ti6O 11The electrical conductivity of the thin film was measured by the four-probe method. The ammeter used for the measurement was a 220 PROGRAMMABLE CURRENT SOURCE (KEITHLEY). The voltmeter used for the measurement was a 6517A ELECTROMETER / HIGH RESISTANCE METER (KEITHLEY). The temperature controller used for the measurement was a cryogenic refrigerator system for electrical measurements PE0-101D-8 (Pascal). The cooling mechanism used for the measurement was a PE-101 type cryosystem. The electrodes used for the measurement were TK paste CN-7120 (Kaken Tech). The temperatures during the measurement were from 10K to room temperature in 10K increments. The pressure during the measurement was about 5 Pa. The current value I was set to +100mA and -100mA, and the average voltage Vave in both directions was calculated to obtain the resistance value as Vave / I. Note that the measurement conditions are not limited to these.
[0048] FIG. 9 shows the conductive film 11 of Example 1, (BaO)2Ti6O 11 FIG. 10 shows the temperature dependence of the electrical conductivity of the thin film of (BaO)2Ti6O 11 A thin film of SrRuO3, which is the conductive film of Comparative Example 1, and a thin film of SrTiO 3-X The temperature dependence of the electrical conductivity of each thin film is shown. 11 The electrical conductivity of the thin film is about 3-4×10 at room temperature. 5 S cm -1 As can be seen by comparing Example 1 with Comparative Examples 1 and 2, (BaO)2Ti6O 11 The electrical conductivity of the thin film was extremely high for an oxide compound. (BaO)2Ti6O 11 The electrical conductivity of the thin film increased with decreasing temperature, indicating metallic behavior.
[0049] FIG. 11 shows the (BaO)2Ti6O 1111 shows the film thickness dependence of the electrical conductivity of the thin film of Example 2. The thin film of Example 2 was made thicker than the thin film of Example 1 in order to eliminate the influence of the interface between the substrate 12 and the thin film, thereby reducing the influence of the interface. As shown in FIG. 11, both the thin films of Examples 2 and 3 exhibited very high electrical conductivity, similar to the thin film of Example 1. It was therefore confirmed that the high electrical conductivity of the thin film of Example 1 was not caused by the interface with the substrate 12.
[0050] FIG. 12 shows a graph of (BaO)2Ti6O as Comparative Example 3. 11 The temperature dependence of the electrical conductivity of the sintered body of (BaO)2Ti6O 11 The sintered body of (BaO)2Ti6O is a polycrystalline body. 11 The electrical conductivity of the sintered (BaO)2 is (BaO)2Ti6O 11 The electrical conductivity of the thin film was lower than that of the (BaO)2Ti6O3 thin film, and it behaved like a semiconductor. The film and the sintered body have the same structure, but there is a large difference in electrical conductivity. 11 As can be seen in the crystal structure of the sintered body, the electrical conductivity is strongly anisotropic, and this is thought to be the cause of the scattering of electrons due to grain boundaries within the sintered body and the formation of an internal electric field.
[0051] FIG. 13 shows the (BaO)2Ti6O calculated by density functional theory (DFT). 11 The Fermi level (E F ) exists near the conduction band edge. (BaO)2Ti6O 11 This suggests that the material has metallic electrical properties. The density of states shown in Fig. 13 is in good agreement with the measured metallic electrical conduction.
[0052] FIG. 14A shows the (BaO)2Ti6O 11 FIG. 14B shows the electron density map in the ac plane of (BaO)2Ti6O 11 The electron density map in the bc plane of (BaO)2Ti6O is shown. The Ti and its number in each of Fig. 14A and Fig. 14B indicate the number of the Ti atom in the unit cell of Fig. 2, i.e., the position. As mentioned above, (BaO)2Ti6O11 has a structure in which a plurality of TiO6 are connected in layers, and has a layered structure in which unit structures and Ba layers arranged between the unit structures are alternately laminated. 11 In this structure, the electrons injected from Ba are spread within the connected TiO6. Figure 14A shows the electrons spreading in the c-axis direction. Figure 14B shows the electrons spreading in the b-axis direction. In the Ba layer, as shown in Figure 14A, the electron density does not spread from the TiO6 layer, but is concentrated in the Ba ions. These results are consistent with the (BaO)2Ti6O 11 This means that the conduction electrons propagate through the clean interior of TiO6, where they are less susceptible to scattering, and this is in good agreement with the observed high electrical conductivity.
[0053] From the above considerations, (BaO)2Ti6O 11 The extremely high electrical conductivity of this thin film is believed to be due to the following factors (1) to (3) and the like. (1)(BaO)2Ti6O 11 has a crystal structure in which one type of unit structure in the form of layers, in which a plurality of TiO6 octahedra are linked in layers, is repeatedly arranged, and Ba is present in the gaps between the unit structures in these unit structures. (2) The valence of Ti is made less than Ti4+ by the additional metal element Ba, so that electrons are injected. (3) The supplied electrons are not scattered by donor impurities and are transported through the interior of clean TiO6 octahedra with little disorder in the unit structure.
[0054] The composition of the metal oxide in the above-mentioned embodiment, the type of substrate used for producing the film, and the like are preferably adjusted to satisfy these conditions.
[0055] [Evaluation of Ti valence] (BaO)2Ti6O 11 The presence of conduction electrons is essential for the electrical conductivity of titanium. As with other titanium oxides, the presence of electrons can be confirmed by the fact that the valence of Ti is less than +4, which is the maximum oxidation number of Ti. (BaO)2Ti6O11 In order to evaluate the Ti valence in the TiAlNbO2, the present inventors measured the electron energy loss spectrum (EELS) using an ARM-200FC (JEOL Ltd.).
[0056] 15A shows the Ti L-edge absorption spectrum (i.e., Ti L-edge) and the O K-edge absorption spectrum (O K-edge). Of the five spectra in the figure, the second from the top is the (BaO)2Ti6O 11 The third spectrum from the top is a spectrum of TiO2. The fourth spectrum from the top is a spectrum of Ti2O3, and the fifth spectrum from the top is a spectrum of TiO. The intensities of peak A and peak B vary depending on the valence of Ti. Therefore, the Ti valence of the metal oxide of the above embodiment can be evaluated from the intensity ratio of peak A to peak B.
[0057] FIG. 15B shows the intensity ratio of peak A to peak B in the EELS spectra of various titanium oxides. 11 The intensity ratio of peak A to peak B in the EELS spectrum of (BaO)2Ti6O in Example 1 was about 0.87 to 0.95. 11 The valence of titanium in the alloy can be evaluated to be Ti3.5+ to Ti3.6+, since the ratio of Ti4+:Ti3+ is approximately 3:2 to 1:2.
[0058] The present disclosure has been described above based on examples. These examples are merely illustrative, and it will be understood by those skilled in the art that various modifications are possible in the combination of each component and each treatment process, and that such modifications are also within the scope of the present disclosure.
Claims
1. A conductive film containing a metal oxide as a main component, The metal oxide has the same components as a compound represented by the following formula (I), and has a crystal structure in which a diffraction peak appears in an X-ray diffraction pattern at the same diffraction angle as a diffraction peak appears in the X-ray diffraction pattern of the compound represented by the following formula (I), (AO) 2 B 6 O 11 (I) In the formula (I), A is a metal element that can have a valence of +1 or +2. In the formula (I), B is a transition metal element that can have a valence of +4 or +5. In the formula (I), O is an oxygen element. The conductive film, wherein the average valence of B in the formula (I) is less than the maximum oxidation number of B.
2. 2. The conductive film according to claim 1, wherein A in the formula (I) is one or more elements selected from the group consisting of Ca, Sr, Ba, Na, K, Rb and Cs.
3. The conductive film according to claim 1 , wherein B in the formula (I) is Ti.
4. B in the formula (I) contains Ti and an element different from Ti, 3. The conductive film according to claim 1, wherein the other element is one or more elements selected from the group consisting of V, Cr, Mn, Fe, Co, Nb, Ru, Pd, Ta, W, Mo, Re, Os, Ir and Pt.
5. The conductive film according to claim 1 , wherein B in the formula (I) is at least one of Ta and Nb.
6. B in the formula (I) contains at least one of Ta and Nb, and another element different from Ta and Nb, 3. The conductive film according to claim 1, wherein the other element is one or more elements selected from the group consisting of Ti, V, Mn, Fe, Co, Ru, Rh, Ir, Mo and W.
7. The present invention relates to a compound having the same components as a compound represented by the following formula (I), and comprising, as a main component, a metal oxide having a crystal structure in which a diffraction peak appears at the same diffraction angle in an X-ray diffraction pattern as a diffraction peak appears in the X-ray diffraction pattern of the compound represented by the following formula (I), (AO) 2 B 6 O 11 (I) In the formula (I), A is a metal element that can have a valence of +1 or +2. In the formula (I), B is a transition metal element which can have a valence of +4 or +5. In the formula (I), O is an oxygen element. The method for producing a conductive film, wherein the average valence of B in formula (I) is less than the maximum oxidation number of B, Providing a substrate; and forming the conductive film on the surface of the substrate by a laser ablation method performed in an atmosphere containing oxygen gas, using a target containing the same element as A in formula (I) and the same element as B in formula (I).
8. In forming the conductive film, the temperature of the substrate is set to 800° C. or more and 1500° C. or less, and the oxygen partial pressure of the atmosphere is 1×10 -6 Pa or more 1×10 -3 The method for producing a conductive film according to claim 7 , wherein the pressure is set to 0.1 Pa or less.
Citation Information
Patent Citations
Method for forming electrically conductive transparent zinc oxide-based film, electrically conductive transparent zinc oxide-based film, and elecrically conductive transparent substrate
JP2012132090A
Titanium oxide crystal and electrode for electricity storage devices that comprises titanium oxide crystal
JP2018199617A
Perovskite oxide containing hydride ion, and method for manufacturing same
WO2013008705A1